The Effect of BBC News Lessons on High School EFL Learners’ Vocabulary Learning - حسن علیزاده محمود علیلو; توران آهور (Journal of Applied Linguistics)
Foreign language vocabulary learning is challenging and requires using an appropriate method. To this end, this study aimed to investigate the effect of listening and viewing BBC News lessons as a teaching and learning tool on high school EFL learners’ vocabulary learning. This quasi-experimental research was carried out in the twelfth grade of Shohada high school in Kalybar city in East-Azarbijan, Iran. Forty two high school EFL learners were chosen as participants from two intact classes. The homogeneity of the classes was checked through a KET test. Then, they were randomly assigned into the experimental (n=19) and control (n=23) groups. Target words were selected from the eight BBC News lessons for both groups. The unfamiliarity of these words to the learners was found through the Vocabulary Knowledge Scale. The experimental group experienced vocabulary learning through watching and listening to the BBC News lessons; while, the control group received the same target words through the traditional method. A vocabulary-based post-test was administrated after the treatment. The result of Independent-Samples t-test on the post-test scores of both groups revealed the significant outperformance of the experimental group compared to the control group. Practical implications are presented to teachers, researchers, and learners.